STUDY OF EPIPHYTIC ALGAE ON Ceratophyllum demersum L. FROM TWO STATIONS AT SHATT AL-ARAB RIVER - A. Al-Saboonchi, Azhar (University of Thi-Qar Journal of Science, 2019)
This study is carried out on the epiphytic algae on Ceratophyllum demersum L. that collected from two different stations at Shatt al-Arab River to investigate the variations in quantity and quality of the epiphyticalgae according to location of aquatic plant. A total of 80 taxa of epiphytic algae were identified at two studied areas; diatoms were the dominant(57taxa) followed by Cyanobacteria (12 taxa) and Chlorophyta (11 taxa). There were variations in the total algal species at two studied stations. Most of the identified algae wereoriginally benthic but some were planktonic such as (Cyclotella spp.; Coscinodiscus sp.; Stephanodiscussp.; Bacillaria paxillifer and Scenedesmus spp.). Six species appeared during the study period; which may be due to their wide range in temperaturetolerance. Higher value of BOD 5 (22-15 mg/l) associated with higher quantity of Ceratophyllum demersum.This conclusion may apply on epiphytic algae which collected from this aquatic plant. This study is carried out on the epiphytic algae on Ceratophyllum demersum L. that collected from two different stations at Shatt al-Arab River to investigate the variations in quantity and quality of the epiphytic algae according to location of aquatic plant. A total of 80 taxa of epiphytic algae were identified at two studied areas; diatoms were the dominant (57taxa) followed by Cyanobacteria (12 taxa) and Chlorophyta (11 taxa). There were variations in the total algal species at two studied stations. Most of the identified algae were originally benthic but some were planktonic such as (Cyclotella spp.; Coscinodiscus sp.; Stephanodiscus sp.; Bacillaria paxillifer and Scenedesmus spp.). Six species appeared during the study period; which may be due to their wide range in temperature tolerance. Higher value of BOD 5 (22-15 mg/l) associated with higher quantity of Ceratophyllum demersum. This conclusion may apply on epiphytic algae which collected from this aquatic plant.